Interaction of PGR Paclobutrazol and Nitrogen Nutrient on Growth and Yield of Potato (Solanum tuberosum L.) Granola L. Variety - Darus, Deisire N. S.; Runtunuwu, Semuel David; Lengkong, Edy Fredy; Tulung, Stella (Jurnal Agroekoteknologi Terapan, 2024)
This study aims to analyze the interaction between paclobutrazol (PBZ) with Nitrogen (N) nutrients on the growth and yield of potato (Solanum tuberosum L.) var. Granola L. It was conducted in Mokobang Village, Modoinding District, South Minahasa Regency. This research was carried out in the form of field experiments and laboratory analysis. The treatment consisted of two factors: A. PBZ at doses: 1) 3 kg PBZ/ha, 2) 3.5 kg PBZ/ha, and 3) 4 kg PBZ/ha. B. Nitrogen nutrient at doses: 1) 200 kg N/ha, 2) 250 kg N/ha, 3) 300 kg N/ha. The placement used RGD and each treatment was repeated 3 times, there were 27 combinations (3 x 3 x 3). The results showed an interaction between the growth and yield of potato plants. Generally, higher doses of PBZ and N increased the growth of plant height, number of leaves, number of branches, leaf wet weight and dry weight, stem wet weight and dry weight, root wet weight and dry weight, plant wet weight and dry weight, and leaf chlorophyll content and tuber yield. The interaction of PBZ and N increased the tuber yield of potato plants per hectare. The highest tuber productivity resulted from the treatment of 4 kg PBZ and 200 kg N/ha (P3N1) at 37.9 tons/ha, while the lowest productivity resulted from the combination of 3 kg PBZ and 250 kg N/ha (P1N2) at 27.3 tons/ha. Keywords: Interaction, Paclobutrazol (PBZ), Nitrogen (N), Solanum tuberosum L. var. Granola L. Abstrak Penelitian ini bertujuan untuk menganalisis interaksi antara paclobutrazol (PBZ) dengan hara Nitrogen (N) terhadap pertumbuhan dan hasil kentang (Solanum tuberosum L.) var. Granola L. Dilaksanakan di Desa Mokobang Kecamatan Modoinding Kabupaten Minahasa Selatan. Penelitian ini dilaksanakan dalam bentuk percobaan lapangan dan analisis laboratorium. Perlakuan terdiri dari dua faktor yaitu: A. PBZ diberikan pada umur 6 MST, dengan dosis: 1) 3 kg PBZ/ha, 2) 3,5 kg PBZ/ha dan 3) 4 kg PBZ/ha. B. pupuk N diberikan pada umur 4 dan 6 MST, dengan dosis: 1) 200 kg N/ha, 2) 250 kg N/ha, 3) 300 kg N/ha. Penempatan menggunakan RAK dan setiap perlakuan diulang 3 kali, terdapat 27 kombinasi (3 x 3 x 3). Hasil penelitian menunjukkan adanya interaksi terhadap pertumbuhan dan hasil tanaman kentang. Umumnya, makin tinggi dosis PBZ dan N meningkatkan pertumbuhan tinggi tanaman, jumlah daun, jumlah cabang, berat basah dan berat kering daun, berat basah dan berat kering batang, berat basah dan berat kering akar, berat basah dan berat kering tanaman, kandungan klorofil daun, dan hasil umbi. Interaksi PBZ dan N meningkatkan hasil umbi tanaman kentang per hektar. Produktivitas umbi tertinggi dihasilkan dari perlakuan 4 kg PBZ dan 200 kg N/ha (P3N1) yaitu 37.9 ton/ha, sedangkan produktivitas terendah dihasilkan dari kombinasi 3 kg PBZ dan 250 kg N/ha (P1N2) yaitu 27.3 ton/ha. Kata kunci: Interaksi, Paclobutrazol (PBZ), Nitrogen (N), Solanum tuberosum L. var. Granola L.